The fortification of encapsulated soy isoflavones and texture modification of soy milk by α-lactalbumin nanotubes. (1st September 2023) - Liu, Bin; Thum, Caroline; Wang, Qimeng; Feng, Chunsong; Li, Ting; Damiani Victorelli, Francesca; Li, Xing; Chang, Ruxin; Chen, Shanan; Gong, Yifu; Li, Yuan
Graphical abstract: Highlights: Nanocarrier of soy isoflavone-loaded α-lactalbumin nanotubes (NT/IFs) was developed. Nanotubes (NT) with high aspect ratio self-assembled from α-lac hydrolyzed peptides. Soy isoflavone (IFs) encapsulated by nanotubes via hydrophobic interactions. The α-lac nanotubes enhanced the viscoelastic property and stability of soy milk. NT/IFs nanocarrier showed high compatibility in fortified soy milk. Abstract: Nanocarriers can improve the dispersibility of hydrophobic bioactive compounds and potentially improve the texture of liquid food formulations. Here, nanotubes (NTs) with a high aspect ratio formed by self-assembly of peptides partially hydrolyzed from α-lactalbumin (α-lac) were used to deliver soy isoflavones (IFs) and modify soy milk texture. IFs encapsulated by nanotube (NT/IFs) via hydrophobic interactions, which had improved dispersibility, with a maximum loading efficiency of 4%. The rheological characterization showed that the nanotubes enhanced the viscoelastic property and long term-stability of soy milk. About 80% of the NT/IFs in soy milk survived simulated in in vitro gastric digestion promoting the release of IFs in the intestinal phase. Overall, this work demonstrated that α-lac nanotubes may be a multi-functional carrier system for hydrophobic compounds providing beneficial changes to functional food texture.